Global supply chain sustainability: an emerging economy suppliers’ perspective - Pereira, Michele Morais Oliveira (2021)
Sustainability has been increasingly necessary for the performance of companies and supply chains (SC) in globalized markets in order to reduce the impacts of their operations, better manage risks and improve their competitiveness. To achieve strategies in this sense, improve the Sustainable Supply Chain Management (SSCM) is essential, which consists of managing interorganizational relations and materials, processes, capital and information throughout SC with objectives focused on sustainability. Particularly in global SCs, most suppliers are based in emerging countries being responsible for many parts of SC activities. Thus, it is necessary to better understand these suppliers' sustainability since most studies address the point of view of buyers from developed countries. This thesis is structured as a set of four scientific articles and its overall aim is to investigate how emerging economy global suppliers manage sustainability and how their sustainability inititiaves affects themselves and global SC sustainability. This is achieved through the four studies by examining the subject from supplier own viewpoint. The study is a qualitative research using mixed research methods as a systematic literature review and a multiple cases studies with interviews and documental analysis as source of data collection. The studied empirical context was the Brazilian coffee industry that was explored due to its importance globally as Brazil is the largest coffee producer in the world that produces around 32% of the total coffee consumed supplying relevant global SCs. It is important highlight that this research was conducted before and during COVID-19 pandemic context which has challenged many different SC players worldwide in terms of strategies and adaptations of operational activities. The findings indicate sustainability certifications and inteorganizational relationships as rich sources of knowledge and learning for these suppliers. It demonstrates that through these relationships, the adoption of sustainability certification programs has enabled emerging economy suppliers to improve their sustainability as well as develop resources, learning and competences in their operation in global SCs albeit in a global disruption. Specifically, the first study found differences between buyers and suppliers’ operational contexts as barrier for suppliers’ sustainability initiatives indicating that buyer companies need to increase their awareness about what has been done by suppliers and how it affects the management of SC sustainability. The second paper presented collaborative practices adopted by suppliers as a strong foundation for sustainability initiatives, internationalization and relational rents for operation in the gobal market. The third study showed the improvement of sustainability in suppliers’ operations as part of the certification programs adoption, moreover competences at individual, organisational and SC level were developed beyond the traditional Triple Bottom Line sustainability dimensions. Finally, the fourth study’s findings indicate that during the COVID-19 pandemic the emerging economy suppliers had an accelerated sustainability learning and changes on their sustainability focus.